2021
DOI: 10.1089/vim.2021.0022
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effects of the Genetic Polymorphisms of Interleukin-10 in Clinical Outcomes of COVID-19

Abstract: Interleukin-10 (IL-10) gene polymorphisms have been associated with severity and outcomes in patients with respiratory and nonrespiratory viral infections. The aim of this study was to assess whether rs1800871 and rs1800872 polymorphisms of IL-10 gene are associated with the clinical outcomes of COVID-19 in a Mexican population. Study subjects were 193 COVID-19 patients. The genotyping was carried out with real-time PCR and serum IL-10 levels were measured with enzyme-linked immunosorbent assay. Logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…In case of IL-10 ( rs1800872) gene polymorphism, a significant protective role of CC genotype was observed in preventing COVID-19 severity among infected patients ( p = 0.010). A study on Mexican population reported a similar finding where frequency of CC genotype was higher in mild (52.1%) as compared to severe COVID-19 patients (50.7%) but their results were not found to be significant [ 22 ]. The frequency of AA genotype was found to be 9.4% and 13.3% in our mild and severe cases respectively which is a bit higher when compared to Mexican COVID-19 patients (5.3% and 10.7%, respectively).…”
Section: Discussionmentioning
confidence: 82%
“…In case of IL-10 ( rs1800872) gene polymorphism, a significant protective role of CC genotype was observed in preventing COVID-19 severity among infected patients ( p = 0.010). A study on Mexican population reported a similar finding where frequency of CC genotype was higher in mild (52.1%) as compared to severe COVID-19 patients (50.7%) but their results were not found to be significant [ 22 ]. The frequency of AA genotype was found to be 9.4% and 13.3% in our mild and severe cases respectively which is a bit higher when compared to Mexican COVID-19 patients (5.3% and 10.7%, respectively).…”
Section: Discussionmentioning
confidence: 82%
“…In addition, HLA‐A*11:01, B*51:01, and C*14:02 alleles constitute the most significant risk alleles predisposing for severity 101 . Other immune molecules, like cytokines and chemokines, were also significantly associated with the majority of the studies 102–105 …”
Section: Resultsmentioning
confidence: 98%
“…101 Other immune molecules, like cytokines and chemokines, were also significantly associated with the majority of the studies. [102][103][104][105] The most significant association signals of another GWAS in UK patients were reported to be harbored in the gene cluster of OAS1, OAS2, and OAS3 (rs10735079), in DPP9 (rs2109069), in IFNAR2 (rs2236757) near the gene TYK2 (rs74956615). 106 DNAH7, CLUAP1, DES, SPEG, STXBP5, TOMM7, and WSB1 have been also associated with COVID-19 mortality in another GWAS.…”
Section: Findings From Genetic Association and Cohort Studies Of Covi...mentioning
confidence: 99%
“…In addition, the significant association of IL‐17A AG (rs2275913), IL17F TT (rs763780), and IL10 AG (rs1800896) SNPs with international severity and death outcome due to the COVID‐19 has been deciphered 73 . Noticeably, IL10 rs1800871 and rs1800872 genotypes among 193 COVID‐19 patients, were not significantly associated with the disease severity 76 (Table 1). IL17 gene polymorphisms have been associated with ARDS, SARS COV, MERS, and SARS‐COV‐2 in which the decrease in the IL17 levels was protective, but increased levels were related to the disease severity.…”
Section: Interleukins Polymorphismsmentioning
confidence: 98%